Migration Characteristics of Heavy Metals in Soil During Water Loss Process - Xu Die; Zhao Shijie; Cai Xiongfei; Wang Ji; Xie Gang; Yu Xinjie; Zhao Shuai (Shuitu baochi tongbao)
[Objective] The migration characteristics of heavy metals in the surface soil of sloping farmland during water erosion process were analyzed in order to provide guidance for soil quality protection and for defense strategies against heavy metal migration and diffusion in karst soil erosion areas in China. [Methods] A simulated rain experiment was used to study loss characteristics of heavy metals (Cu, Ni, Cd, and Cr) from runoff and erosion in farmland under different slope conditions (10°, 15°, 20°, and 25°) and rainfall intensities (50, 70, 90, and 120 mm/h). [Results] ① Initial runoff and sediment yield increased with increasing of rainfall intensity and slope, then tended to gradually become stable. The critical slope for sediment yield was 20° under different rainfall intensities and slopes; ② Heavy metals mainly existed in granular form in the erosion process of topsoil, and migration amount was proportional to rainfall intensity. Heavy metal loss in granular form first reached a peak value under a rainfall intensity of 120 mm/h and a slope of 20°. Dissolved heavy metals varied with rainfall intensity, except for dissolved Ni that reached a maximum variation range of 0.0044 mg/L at 50 mm/h. Cu, Cd, and Cr all reached a maximum variation range of loss at 70 mm/h, and the maximum variation range of Cr was 0.0098 mg/L. The loss of dissolved heavy metals had no obvious relationship with slope change. ③ The heavy metal particle loss was related to sediment yield, and the high coefficient of determination for Cr (R2=0.99) indicated that sediment yield could well predict Cr particle loss. [Conclusion] 20° is the critical slope for sediment yield, and that migration of heavy metals is mainly in granular form. The fitting effect between sediment yield and heavy metal elements (Cu, Ni, CD, and Cr) is good, indicating that there is a strong correlation between heavy metal elements (Cu, Ni, CD, and Cr) and sediment yield.